The fashionable dancer's casket; or, The ball-room instructor. A new and splendid work on dancing, etiquette, deportment, and the toilet. - Durang, Charles (Philadelphia, Fisher & Brother, 1856)
Although Charles Durang was a well-known Philadelphia dancing teacher and the son of famed American dancer John Durang, very little of this manual originates from the pen of the author. He acknowledges that the dances contained in the book are by the "celebrated teachers of Paris and London." Additionally, the sections on etiquette, deportment, and dress stem from "Mrs. Henderson's treatise." The manual includes descriptions of the popular ballroom dances of the day--quadrilles, polka, waltz, schottisch, gorlitza, and Cellarius waltz.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals